Texting, and Digital Multiliteracies: SMS and Beyond - Christiansen, Sidury (CIEX JOURNAL, 2016)
By framing this discussion in a literature review and through the lens of multiliteracies, this pedagogical presentation offers several ideas to encourage ELT professionals to harness the popularity of texting and to promote critical awareness of language used among digital platforms through integration of textese and situated academic and social collaboration via SMS into their curriculum. The latter behaviors will become integral to student persistence in higher academic areas. This presentation explains ways that texting helps to develop English language skills in authentic, modern ways.